Computer Support for Data Analysis - Lunneborg, Clifford E (Research Methods for Postgraduates, 2016)
In this 21st century, no post‐graduate student will complete the analysis of his or her research data without turning to a computer. The computer provides invaluable support to the research student in the analysis of data. The increase in amount of computing support for data analysis prompts a second warning: statistical computing resources should be identified while designing the research. Most research programs will profit from exploratory as well as confirmatory data analyses. Briefly, confirmatory analyses are those that answer the questions that drove your research. Exploratory analyses provide clues about how better to design your next study. There are statistical procedure packages and statistical languages. Genstat is the product of researchers at the Rotham‐sted Experimental Station and is distributed by the Numerical Algorithms Group (NAG). Statistical Package for the Social Sciences (SPSS) boasts a host of standard parametric and nonparametric statistical tests and is widely used for standard analyses of variance.